Natural Colorants from Fungi - Mussagy, Cassamo U.; De Oliveira, Fernanda [UNESP]; Santos-Ebinuma, Valeria C. [UNESP] (Wiley, 2023)
The search for natural colorants has grown increasingly and microorganisms are a promising source mainly due to the development of biotechnology and bioprocess engineering. In nature, several microorganisms are capable of producing natural colorants as a result of their development. However, fungi are a very versatile group that can produce an amazing range of colorants with different hues of colors and properties, such as antioxidant and antimicrobial characteristics. These compounds find several promising applications in the food, feed, cosmetic, and textile industries. So, this chapter explores the more relevant fungal colorants (used in industry and scientific community) to provide readers with a brief knowledge of their biosynthesis, toxicity, and industrial application.